Pemberdayaan Perempuan melalui Pembuatan Bubur Sagu pada Pelayanan Perempuan Jemaat GPM Hatiwe Besar - Haumahu, Alberthina Abetsi; Noya, Ferdinanda Sherly; Latuputty, Lussy; Lokolo, Lambertus Johanes (Jurnal Pengabdian Arumbai, 2025)
The women's empowerment program implemented by the Women’s Ministry Group (WPP) of the GPM Hatiwe Besar Congregation aims to address the lack of innovation in processing sago flour into economically valuable food products. Sago, a traditional staple in Maluku, has mostly been used in conventional forms and has not yet been developed into attractive, competitive food products. In response, the community engagement team conducted a culinary training focused on creating chocolate ganache sago porridge as a potential local souvenir product. The training consisted of two sessions: a presentation on tools, ingredients, and preparation steps, followed by hands-on practice. An interactive lecture method was combined with demonstrations to increase participant engagement and understanding. Evaluation showed a significant improvement in technical skills, self-confidence, and collaborative spirit among participants. This program is expected to spark culinary innovation based on sago, strengthen family economic independence, and promote the sustainable use of local resources.